Comments on the Article “[6]-Shogaol Induced Calcium Signal in Rat Insulinoma Cells” - Aswani, Yashant; Raut, Sanket; Ambadipudi, Lohith (JOP. Journal of the Pancreas, 2014)
No abstract available Image: Ginger flower